News media vs. FRED-MD for macroeconomic forecasting - Jon Ellingsen; Vegard Høghaug Larsen; Leif Anders Thorsrud (Norges Bank, 2020)
Using a unique dataset of 22.5 million news articles from the Dow Jones Newswires Archive, we perform an in depth real-time out-of-sample forecasting comparison study with one of the most widely used data sets in the newer forecasting literature, namely the FRED-MD dataset. Focusing on U.S. GDP, consumption and investment growth, our results suggest that the news data contains information not captured by the hard economic indicators, and that the news-based data are particularly informative for forecasting consumption developments.
hdl:11250/2690107
Keywords: C53; C55; E27; E37; 330; Forecasting; Real-time; Machine Learning; News; Text data